ChemInform Abstract: Evaluation of Structural Effects of Acyclic and Macrocyclic Ligands Derived from (R, R)‐Cyclohexane‐1, 2‐diamine in the Enantioselective Cu(II)‐Catalyzed Henry Reaction. Issue 17 (April 2015) - Cerisoli, Lucia; Grilli, Stefano; Savoia, Diego
Abstract Two new ligands with acyclic and macrocyclic structure are synthesized and tested in the Henry reaction of benzaldehyde with nitromethane.